NEED ANALYSIS ON ASSESSMENT BASED E-LEARNING PLATFORM IN READING CLASS FOR VOCATIONAL STUDENTS AT EAST LAMPUNG - Nyanuar Algiovan (Paedagogia: Jurnal Pendidikan, 2022)
Assessment and the learning process become two intertwined concepts that are impossible to separate. When compared to the other three abilities, reading skills are the most important in English learning. In order to meet the demands of modern teaching development, information and communication technology is required for English language instruction and assessment. The purpose of this study is to examine the requirements of both learners and pursuers in terms of the use of information and communication technology in reading instruction assessment (Reading Assessment). This current study used two data collection technique, namely questionnaires and interviews analyzed quantitatively and qualitatively. Respondents in this study were selected by purposive sampling involving 70 students and 5 teachers in vocational schools. The results of this study found that (1) The students’ goal and necessities differ, (2) The students are at beginner level at reading skill and have reading word and sentences fluently and correctly, (3) They want familiar contents based on their life, environment and major,(4) The need of information and communication technology both for learning and assessing and (5) Through the product, the English learners would be learning, collaborative and independent. The researcher advised for further researcher to conduct the development the information and communication technology for teaching and assessing English learners in vocational schools.